Facilitating factors for community-managed wastewater systems in the Kanata metropolitan region, Bolivia. (December 2021) - Helgegren, Ida; Minelli, Francesca; McConville, Jennifer; Landaeta, Graciela; Rauch, Sebastien
Abstract: Provision of safe sanitation services is a major challenge in low and middle-income countries where adequate wastewater management is almost entirely lacking or insufficient. Community-managed wastewater systems are increasingly seen as part of the solution to this challenge. There is, however, a lack of in-depth understanding regarding how these communal systems are affected by external factors. Through a qualitative case study of the wastewater sector of the Kanata metropolitan region, Bolivia, this paper aims to contribute to filling this knowledge gap. A variety of data collection and analysis procedures resulted in two main outcomes. First, a shared common vision regarding the development of the wastewater sector and the role of community actors was highlighted as crucial for strengthening communal wastewater management. Secondly, facilitating factors that promote community-managed wastewater services were identified, i.e. financing possibilities, technical support, legal support, formal and informal networks, continuous dialogue, trust, compatibililty with local institutions, control of territory and availability of contractors and builders. The results provide guidance for both policymakers and development practitioners that aim to strengthen community-managed wastewater systems, as well as contribute to increased theoretical understanding.